Factors Affecting Digital Financial Service Adoption in Bangladesh: Evidence from SEM-ANN Approaches - Nafis Sadik; Md. Mominur Rahman (Journal of Risk Analysis and Crisis Response (JRACR))
The rapid growth of Digital Financial Services (DFS) has revolutionized the financial landscape in developing countries, including Bangladesh. Despite its growing importance, understanding the factors influencing DFS adoption remains limited, particularly when leveraging advanced analytical frameworks. This study investigates the key drivers affecting the adoption of DFS in Bangladesh by employing Structural Equation Modeling (SEM) and Artificial Neural Network (ANN) approaches. Using survey data collected from 340 DFS users, the SEM analysis validates the proposed relationships, identifying financial literacy, trust, access to capital, digital payment usage, and digital financial inclusion as significant factors driving DFS adoption. ANN modeling further highlights the relative importance of these predictors, revealing financial literacy as the most influential factor, closely followed by digital financial inclusion, trust in digital financial services, access to capital and digital payment usage. This dual-method analysis provides nuanced insights for policymakers, financial institutions, and technology providers, aiming to enhance DFS adoption and promote financial inclusion in Bangladesh.